U.S.-led bombardement challenges Islamic State's hold on eastern Syria: But without addressing the roots of the conflict, the group will remain hard to beat - Khaled Yacoub Oweis (Stiftung Wissenschaft und Politik (SWP), 2014)
In July 2014, the so-called Islamic State solidified its hold on large parts of the Euphrates river basin in eastern Syria, expelling its al-Qaeda rivals from the region, weeks after having captured the city of Mosul in neighboring Iraq and having declared a caliphate. The advance undermined the pro-Assad Shi'ite-dominated government in Baghdad and prompted Syrian regime forces to confront the group. In September 2014, a U.S.-led air campaign against the Islamic State in Iraq expanded into Syria. It was met by dismay on the part of Syria's opposition about the lack of pressure on President Bashar al-Assad as jihadists feed on Sunni resentment against his minority Alawite rule. This has increased the urgency for forging an international solution to Syria's civil war that not only addresses the jihadist dimension but also includes a strategy to reclaim the east - namely one that provides an alternative to Islamist militancy and the Assad family's reign. (SWP Comments)
Keywords: 320